Understanding informatics in continuing vocational education and training data in Germany - Jens Dörpinghaus [Verfasser]; Binnewitt, Johanna [Verfasser]; Samray, David [Verfasser]; Hein, Kristine [Verfasser] (My University, 2024)
„Objectives: The purpose of this study is to reveal the importance of informatics in continuing vocational education in Germany. The labour market is a field with diverse data structures and multiple applications, for example connecting jobseekers and trainings or jobs. The labour market heavily relies on vocational education and training and advanced vocational qualification to meet challenges, e.g., digitalization. Study Methods: Since continuing vocational education and training (CVET) is a structurally important lever for the digital transformation of work, this article presents a methodological procedure for content analysis that provides information about the significance of computer science in unregulated continuing education offerings and in formal continuing education regulations. Findings: The question of the extent to which continuing education programs include informaticss topics is investigated, assuming that they can be found in continuing education as cross-cutting topics in a wide variety of thematic contexts. Our results indicating the need for training in computing education. At the same time, computing education offers the highest share of unregulated CVET programs. This could reflect the fact that training and further education regulations in Germany are designed open to technology. Conclusions: We present a novel and unique approach to analyze the importance of informatics and digitalization in CVET advertisements and official regulations for the same.“ (authors‘ abstract; BIBB-Doku)
Keywords: S 1.5.2 Berufliche Weiterbildung; 370; Berufliche Weiterbildung; Weiterbildungsangebot; Digitalisierung; Informatik